On the Origins of Diffusion MRI Signal Changes in Stroke - Blackband, Stephen J.; Flint, Jeremy J.; Hansen, Brian; Shepherd, Timothy M.; Lee, Choong H.; Streit, Wolfgang J.; Forder, John R. (Frontiers in Neurology, 2020)
MRI is a leading diagnostic technique especially for neurological studies. However, the physical origin of the hyperintense signal seen in MR images of stroke immediately after ischemic onset in the brain has been of debate since it was first demonstrated in 1990. In this article we hypothesize and provide evidence that changes in the glial cells, comprising roughly one half of the brain volume, accompanying ischemia, are the root cause of the MRI signal change. Indeed, a primary function of the glial cells is osmoregulation in order to maintain homeostasis in the neurons and nerve fibers for accurate and consistent function. This realization also impacts our understanding of signal changes in other tissues following ischemia. We anticipate that this paradigm shift will facilitate new and improved models of MRI signals in tissues which will in turn impact clinical utility.